2005
DOI: 10.1536/ihj.46.181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated Plasma Total Homocysteine Concentration on Coronary Atherosclerosis in Chinese Patients With Acute Myocardial Infarction Undergoing Primary Coronary Intervention

Abstract: SUMMARYElevated plasma total homocysteine (tHcy) has been considered to be a new risk factor for coronary atherosclerotic disease. However, the association has not been proven indisputably, and the strength of the relationship and the interaction of plasma tHcy with other conventional risk factors remain uncertain in the clinical setting of acute myocardial infarction (AMI). The aim of this study was to investigate whether an elevated plasma level of tHcy is an independent predictor of the late stage of corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…[7][8][9]19) We were not able to investigate the cause of elevated Hcy levels in our patients. We also did not notice any major clinical adverse events, probably due to the small study group and relatively short observation period.…”
Section: Discussionmentioning
confidence: 90%
“…[7][8][9]19) We were not able to investigate the cause of elevated Hcy levels in our patients. We also did not notice any major clinical adverse events, probably due to the small study group and relatively short observation period.…”
Section: Discussionmentioning
confidence: 90%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Many issues regarding the mechanism of action of homocysteine in the pathogenesis of arteriosclerosis and thrombotic diseases remain unclear. However, possible causes include vascular endothelial dysfunction, [17][18][19][20][21][22] smooth muscle cell growth, [23][24][25] and an increase in blood clotting activity in vascular walls.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] A high plasma homocysteine level has been shown to promote arteriosclerosis and to be an independent risk factor in the development of cardiovascular disease. [9][10][11][12][13][14] In a cohort of patients in the Framingham Heart study, a high plasma homocysteine level was shown to be a predictor of heart failure in adults who had not yet experienced myocardial infarction. 15) However, the relationship between heart failure and homocysteine levels in patients with AMI has not been reported.…”
mentioning
confidence: 99%
“…In the Brazilian population, characterized by ethnic heterogeneity 21 , the results of studies involving plasma homocysteine levels and CAD are equally controversial. It is well to point out that most authors consider hyperhomocysteine as an independent risk factor for CAD 22 . Table 1 shows that plasma homocysteine levels were significantly higher in patients with severe atheromatosis, compared with the control group (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%